1985
DOI: 10.1136/hrt.53.5.541
|View full text |Cite
|
Sign up to set email alerts
|

Pacing in children.

Abstract: Fourteen children had a permanent pacemaker implanted between May 1967 and July 1983. Postoperative complete heart block was the indication in nine cases, congenital complete heart block in three, and sick sinus syndrome in two. Two patients died, one suddenly and one after aortic valve replacement. A total of 48 pulse generators were implanted; five patients were given an isotopic pacemaker. Twelve patients had epicardial leads implanted initially, and two received a transvenous endocardial system. The lead s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1987
1987
2003
2003

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…4 Ector et al reported six fractured leads in 14 children having multiple systems over 16 years but did not record the causes. 5 Previous work has shown that helically wound leads are more flexible and resistant to fractures than are straight ones.6 The mechanical stresses in a helical pacing lead relates to several factors, and modem leads optimise design features aimed at minimising these stresses. The use of platinum alloys with better shear modules and shear stress characteristics and of smaller diameter wires with increased radius of the helical turns increase lead flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…4 Ector et al reported six fractured leads in 14 children having multiple systems over 16 years but did not record the causes. 5 Previous work has shown that helically wound leads are more flexible and resistant to fractures than are straight ones.6 The mechanical stresses in a helical pacing lead relates to several factors, and modem leads optimise design features aimed at minimising these stresses. The use of platinum alloys with better shear modules and shear stress characteristics and of smaller diameter wires with increased radius of the helical turns increase lead flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…Impl./Jahr Andere Autoren geben bei der Indikation zur Schrittmacherimplantation die gleiche Relation zwischen operativ und nicht operativ bedingter Rhythmusstörung an (vgl. 2,5,17,18,20,21). Auch bei Goldman (10) zeigt sich bei den Rhythmusstörungen nach Herzoperation die Unterscheidung in Früh-und Spät-Implantation.…”
Section: Dieunclassified